Pregnant Women's Preparedness in Facing Earthquakes Disaster Risk - Diah Nur Anisa; Endah Tri Wulandari; Istinengtiyas Tirta Suminar (GLOBAL HEALTH SCIENCE GROUP, 2025)
Earthquake disasters can pose many challenges for pregnant women, namely a lack of access to prenatal care and emergency medical services needed. In emergency disaster conditions, what must be of special concern to pregnant women is the safety and well-being of the baby in their womb. This study aims to determine how prepared pregnant women are in facing the risk of earthquake disasters. This study employs a qualitative phenomenological research approach. The phenomenological approach in qualitative research focuses on the essence of life experiences or phenomena that can be observed or experienced by people from different perspectives. This study involved 5 pregnant women. Data collection techniques were carried out using semi-structured interviews. The instrument used was an interview guide for pregnant women's preparedness to face earthquake disasters. The data analysis used is Colaizi analysis. There are 4 themes, namely the highest risk is earthquakes, pregnant women as a vulnerable group, the preparedness of pregnant women, and being prepared for childbirth. The good preparedness of these pregnant women demonstrates that they are aware of the high-risk area for earthquake disasters and are ready for whatever may happen, including childbirth in disaster conditions.